2020
DOI: 10.1091/mbc.e19-10-0564
|View full text |Cite
|
Sign up to set email alerts
|

Abl signaling directs growth of a pioneer axon inDrosophilaby shaping the intrinsic fluctuations of actin

Abstract: Live imaging reveals that a forward bias of the stochastic actin fluctuations in the distal part of an axon drives axon extension by advancing the protrusive, filopodial domain of the growth cone. The actin mass is itself shaped by guidance signaling via Abl tyrosine kinase, which regulates growth cone length and minimizes its disorder.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…The function of guidance cue-dependent signaling is to modulate the organization of the actin core within that growth cone, and the spatial relationship between that actin core and the regional localization of filopodial dynamics, to regulate growth cone advance. Just what are the detailed changes that Abl induces in actin organization and how they in turn produce directed extension of the axon is the topic of the accompanying paper (Clarke et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The function of guidance cue-dependent signaling is to modulate the organization of the actin core within that growth cone, and the spatial relationship between that actin core and the regional localization of filopodial dynamics, to regulate growth cone advance. Just what are the detailed changes that Abl induces in actin organization and how they in turn produce directed extension of the axon is the topic of the accompanying paper (Clarke et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Profiles were extracted from images captured every 3 min. Actin distributions from four individual time points are shown separated below to highlight actin advance by "inchworming" (see accompanying paper [Clarke et al, 2020] for further discussion of this phenomenon); actin profiles of all individual time points are also presented as a gallery of images in Supplemental Figure S2. (G) Scatter plot of the positions of maximum protrusion density vs. maximum actin intensity along the axon; n = 338 time points from 14 individual trajectories; r is Pearson correlation; p is by paired t test.…”
Section: Live Imaging Of the Tsm1 Pioneer Axon In Its Native Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we favor a model of Htt acting as an inhibitor of Abl kinase activity during normal MB axonal growth ( Fig 7 ). Abl activity in axons needs to be maintained within rather narrow limits [ 32 , 33 ]. These two recent studies show that either increase or decrease of Abl activity cause disorganization of actin structure in the growth cone and prevent the orderly oscillation of growth cone actin that is the motor for growth cone advance and thus axon extension.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the precise level of Abl activity is critical to its axonal function, with loss- and gain-of-function both leading to severe defects in neural patterning [ 29 31 ]. Recent experiments revealed the cell biological and biophysical basis of this relationship, showing that either increased or decreased levels of Abl activity induce disorder in growth cone actin and thereby greatly augment the frequency of stochastic errors in growth and guidance [ 32 , 33 ]. Of particular relevance here, Abl has been implicated in axonal arborization and growth in the Drosophila brain [ 34 ], including the MBs [ 5 ], though the precise role of Abl in normal MB development has not been documented.…”
Section: Introductionmentioning
confidence: 99%